Supporting Caregivers of Rural Veterans Electronically (SCORE). Issue 3 (20th July 2016) - Hicken, Bret L.; Daniel, Candice; Luptak, Marilyn; Grant, Marren; Kilian, Shirley; Rupper, Randall W.
Abstract: Background: The increasing prevalence of dementia, including among rural veterans, highlights the improved outcomes possible for caregivers who receive effective support. However, providing these complex interventions in rural areas presents challenges. Internet‐based and telephone‐based caregiver support can potentially expand access to effective support. Methods: We designed a multisite intervention for caregivers of veterans with dementia. Caregivers were stratified into 2 cohorts based on their use or nonuse of the Internet. Each cohort was then randomized to either a technology or telephone‐delivered support group within each cohort. All groups had a care manager who monitored the 4‐ to 6‐month multicomponent program of assessments, educational content, and skills training. Caregiver outcome measures included burden, anticipatory grief, depression, family conflict, and a desire to institutionalize the care recipient. Results: The majority of comparative effectiveness outcomes were not different between caregivers receiving technology interventions versus those receiving telephone‐delivered support. This was true for the 68% of caregivers using home Internet and the 32% nonusers, as well as the 53% rural versus 47% urban caregivers. For experienced Internet users, a meaningful difference in the Marwit Grief Inventory was noted for caregivers receiving Internet versus telephone support, particularly for the Isolation Subscale. Conclusion: This study demonstrates the feasibility and acceptability of using a variety of modalities to deliver caregiver support to a group of largely older, rural, spousal caregivers of veterans with dementia. The potential for reducing isolation for caregivers capable of receiving this intervention through the Internet is a promising finding.